THALASSOTHERAPY AND PROPHYLAXIS IN BRONCHIAL ASTHMA - Georgi Georgiev; Galina Мratskova (Science & Research)

(untitled)
Bronchial asthma is a common disease of the respiratory system in children and adults. The disease proceeds with repeated symptoms of airway obstruction, cough and shortness of breath, which are paroxysmal in nature. To reduce the frequency of attacks and the severity of the disease in non-attack periods, it is recommended to apply sea treatment (Thalassotherapy) in combination with other natural physical factors. The purpose of this report is to investigate the possible therapeutic effects of the application of natural physical factors and Thalassotherapy in bronchial asthma. Materials and methods: a review of available scientific articles in Bulgarian and in foreign literary sources, which contain publications on the application of natural physical factors and sea treatment in patients with bronchial asthma, was made. Results: During the review of the scientific literature at Pub Med, Google Scholar, Science Direct, evidence for the effectiveness of the application of natural physical factors (procedures such as: aerotherapy, inhalations, aeroheliotherapy), including Thalassotherapy in patients with bronchial asthma, was found. Sea treatment, carried out outside the acute period of the disease, is an important part of the preventive and rehabilitation programs for Bronchial asthma. Conclusion: Application of Thalassotherapy and treatment with natural physical factors can reduce the severity of bronchial asthma by non-specific reduction of allergic hyperreactivity of the body, reduction of inflammatory reactions of the respiratory system and possible other focal areas of inflammation (chronic rhinitis, rhinosinusitis, tonsillitis and etc.), and can lead to an improvement in the functional state of the lungs and external breathing.